Relationship Between Body Mass Index And Physical Fitness Level (VO2 Max) In The Family Empowerment And Welfare Driving Team Of Pasir Gaok Village, Bogor Regency - Muh Amrul Ta'gan; Bazzar Ari Mighra; Heni Widyaningsih (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research aimed to determine the relationship between Body Mass Index and Physical Fitness Level (VO2Max) in the Family Welfare Empowerment Team (TP-PKK) in Pasir Gaok Village, Bogor Regency. This research uses quantitative descriptive research. The approach in this research uses a survey method with correlation techniques. The physical fitness measurement test uses the Rockport test method to determine the level of physical fitness (VO2 max). The population in this research was the Family Empowerment and Prosperity Mobilization Team (TP-PKK) in Pasir Gaok Village, Bogor Regency, totaling 20 people. The sampling technique is purposive sampling with the following samples: 1. Active members (TPPKK) of Pasir Gaok Village, Bogor Regency, 2. No injuries, 3. Age 20 years and over, 4. Healthy. The data taken are age, height, weight, blood pressure, and VO2 Max. The analysis uses descriptive analysis techniques. The results of the research show that there is a relationship between body mass index and physical fitness level (VO2Max), the results of measuring body mass index are in the normal category of as many as 17 members or 85%, while for the results of physical fitness level (VO2 Max), there are still many who get the sufficient category as many as 14 members or 70%. Based on the results of research analysis data on the relationship between body mass index and physical fitness level (VO2Max) in the Family Empowerment and Welfare Mobilization Team (TP-PKK) in Pasir Gaok Village, Bogor Regency, it was found to be (-0,295). This shows that the relationship between body mass index and physical fitness level (VO2Max) in the Family Empowerment and Welfare Team (TP-PKK) in Pasir Gaok Village, Bogor Regency is in the weak category.